Ten-Year Experience With the Anterior Approach to Total Hip Arthroplasty at a Tertiary Care Center - Gofton, Wade T.; Ibrahim, Mazen M.; Kreviazuk, Cheryl J.; Kim, Paul R.; Feibel, Robert J.; Beaulé, Paul E. (The Journal of arthroplasty, 2020)
The anterior approach (AA) to total hip arthroplasty (THA) has advantages for patients and healthcare providers. However, some studies have reported high rates of adverse events when introducing AA-THA. This was not consistent with our center’s experience, where 4 senior surgeons safely introduced AA-THA into practice. The purpose of this study is to define the adverse event rates associated with the introduction of AA-THA by a group of experienced surgeons at a single tertiary care center and define experiential factors that may modify adverse event rates. Retrospective review of prospectively collected data for an observational cohort of all patients undergoing a THA between 2006 and 2017 was conducted. Four senior surgeons at a single institution operated on 1087 primary elective hips using AA-THA. Between 2006 and 2016, AA-THA rose from 1.5% to 53.2% of annual THA. Adverse events included intraoperative events, early postoperative periprosthetic fractures, dislocation, implant failure, early infection, and wound complications. We observed an overall 90-day adverse event rate of 6.4% (of 1087 hips). The adverse event rate was 41.6% (of 12 hips) in the first 12 months of the study period and 3.6% (of 166 hips) in the final 12 months of the study period reviewed. Sixty hips (5.5%) required a reoperation with or without revision of components, 1 (8.3%) in the first 12 months of the study period and 1 (0.6%) in the final 12 months of the study period. Infection and wound complications were the most common causes of reoperation at 1.8% for all cases (20 hips). Higher rates of adverse events are associated with early procedures (n ≤ 15) for all surgeons but showed no statistically significant impact on 5-year survival rate. Our experience demonstrates that AA-THA can be introduced into practice with an acceptable adverse event rate when compared with other approaches to THA. As expected the incidence of adverse events is higher in the early part of the learning curve. Surgeon mentoring in the first 20 cases should be considered to minimize risk of adverse events. Therapeutic Level III.